The Role of Leadership and Digital Culture in Enhancing Organizational Sustainability in Higher Education: A Case Study at Universitas Kristen Indonesia Tomohon - Sammy Rommy Novie Korua; Peggy Adeline Mekel; Priskila Gissela Marlia Walangitan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the interaction between leadership, digital culture, and organizational sustainability within the context of digital transformation at Universitas Kristen Indonesia Tomohon (UKIT), a faith-based higher-education institution in Eastern Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews with 15 key informants, strategic document analysis, and observational notes. Thematic analysis revealed that value-driven transformative leadership serves as the central catalyst for digital adoption, with senior leaders actively modeling digital practices and framing technology as an extension of the Christian mission and service. The concept of